Acceleration Breaks the Cells Defense Mechanisms against Vibration in Anthemis gilanica Calli - Halimeh Hassanpour; Vahid Niknam; Sadaf Salami (International Journal of Agronomy)
Vibration is a mechanical stress which happens in nature and affects many biological aspects of plants. In this research, the effect of acceleration and vibration was investigated on some physiological and biochemical responses of Anthemis gilanica in vitro. Calli were induced from leaf (LS) and root segments (RS) and were applied to different frequencies of vibrations (0, 50, and 100 Hz) and accelerations (1, 2, and 4 g) on the A. gilanica calli for 30 min. Results showed that vibration significantly increased relative water content (RWC), growth parameters, protein and proline contents, ascorbate peroxidase (APX), peroxidase (POX), and superoxide dismutase (SOD) activities and decreased total carbohydrate, malondialdehyde (MDA), H2O2 contents, and polyphenol oxidase (PPO) activity in both LS and RS calli. Inversely, increase of acceleration in vibrated calli decreased growth parameters, RWC, protein content, and POX activity and induced proline and carbohydrate accumulations, SOD, APX, and PPO activities as compared to vibration alone. Different responses of two callus types were observed, and the highest growth, protein content, and membrane stability were observed in LS calli as compared to RS calli. It found that high acceleration amplitude intensified the resonance effect of vibration by induction of lipid peroxidation and oxidative stress damage in A. gilanica.